Behavioral Effects of Antiepileptic Drugs - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
Parental responses to a Child Behavior Checklist were compared before and after changing antiepileptic therapy in an open, parallel design study in the School of Pharmacy and Departments of Neurology and Pediatrics, School of Medicine, University of North Carolina, Chapel Hill, North Carolina.